Refeeding Syndrome in Malnutrition – Diagnosis and Management - Aini, Mei Tsarah; Yuliarti, Klara (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2024)
Background: Refeeding Syndrome (RS) is a one of the potentially life-threatening complications in malnourished children. The diagnosis of RS is often challenging due to its diverse clinical manifestations. A comprehensive understanding of the risk factors, sign, symptoms and the management of RS is important to reduce morbidity and mortality. Discussion: The management of malnutrition consists of a ten-step process divided into three phases. Adherence to this protocol is important to mitigate the risk of RS. RS is a metabolic complication that occurs when malnourished children rapidly reintroduced to nutrition. This condition is characterized by a shift of electrolytes from the extracellular to the intracellular, leading to hypophosphatemia, hypokalemia, hypomagnesemia, and thiamine deficiency. Children with RS require aggressive electrolyte and vitamin supplementation, followed by a cautious nutritional re-initiation. A gradual approach to nutritional reintroduction and electrolyte supplementation, are a critical preventive measure of RS. Conclusion: All malnourished children are at risk of RS. Recognizing its risk factors and watchful monitoring are essential for early detection and prevention of RS.